WTO Analytical Index : Guide to WTO Law and Practice / Legal Affairs Division, World Trade Organization. (Cambridge University Press, 2012)
The WTO Analytical Index is a comprehensive guide to the interpretation and application of the WTO Agreements by the Appellate Body, dispute settlement panels and other WTO bodies. It contains extracts of key pronouncements and findings from tens of thousands of pages of WTO jurisprudence, including panel reports, Appellate Body reports, Article 21.3(c) awards and Article 22.6 decisions. This unique work will be of assistance to anyone working in the field of WTO law, including lawyers, economists, academics and students. It is produced by the Legal Affairs Division of the WTO Secretariat with contributions from other divisions of the Secretariat and the Appellate Body Secretariat. The third edition of the WTO Analytical Index covers developments in WTO law and practice over the period January 1995 to September 2011.